Modeling and optimization of moisture diffusion of paddy and brown rice during thermal soaking - Chaiwat Rattanamechaiskul; Nittaya Junka; Preeda Prakotmak (My University, 2023)
Abstract In this study, a method involving soaking paddy and brown rice in hot water at different durations and temperatures is investigated. Data are acquired to develop a mathematical model to determine the most appropriate soaking conditions through simulation. Results show that higher soaking temperature at 60 °C yield higher moisture diffusion than lower temperature at 40 °C. The soaking times of paddy until the final moisture was attained at temperatures of 40 °C, 50 °C, and 60 °C were 10, 8, and 6 h, respectively. The dehusking process from paddy to brown rice can decrease soaking time to 7, 5, and 3 h, respectively, compared with that of paddy at the same temperature. The mathematical modeling can reveal the diffusion mechanism inside the grain and accurately predict the suitable soaking condition by brown rice at soaking temperature of 60 °C for 1.5 h. When this condition is used, the specific energy consumption of the soaking process can be reduced to 0.295 kWh kg −1 which is the lowest value in the scope of study. After steaming by commercial process, soaked brown rice is completely generated starch gelatinization as parboiled rice. Practical applications Soaking is one of the most important procedures in the production of parboiled rice. It requires a significant amount of time as well as affects the specific energy consumption (SEC) and product quality at the final stage. Experiment results are used to develop a mathematical model to determine the most appropriate soaking condition. The shortest time possible to achieve the appropriate grain moisture while maintaining the lowest SEC is desired. Data are acquired to devise methods for reducing the time and energy required to produce parboiled rice.
Keywords: Brown rice; Steaming; Food composition and properties